Vertical Effects of Fiscal Rules - The Swiss Experience - Heiko T. Burret; Lars P. Feld (Center for Economic Studies and ifo Institute (CESifo), 2014)
Formal fiscal rules have been introduced in many countries throughout the world. While most studies focus on intra]jurisdictional effects of fiscal rules, vertical impacts on the finances of other levels of governments have yet to be explored thoroughly. The paper investigates the influence of Swiss cantonal debt brakes on municipal finances during the years 1980]2011 by examining cantonal aggregated and disaggregated local data. A Difference]in]Differences estimation (two-way fixed effects) provides little evidence that budget constraints at the cantonal level affect municipal finances and fiscal decentralization, respectively.
Keywords: H60; H77; H74; H72; 330; fiscal rules; vertical effects; fiscal shocks; decentralization; sub-national finances